Integration and standardization of business and management processes for consumer products utilizing business process reengineering approach - Allan Mathews (2007)
The main objective of this thesis is to determine whether Business Process Reengineering (BPR) can be utilized to standardize and integrate business and management processes of three subsidiary companies at the branch level within a large multinational holding company. Although the functions of procurement, selling, order processing, credit management, warehousing and distribution, and collection are the same in the three subsidiary companies, there were differences as to how the processes were carried out. The objective of the holding company is to portray to the customers that it is one entity. The problem situation resulted amongst other matters, confusion among the customers. Top management in line with the principles of BPR decided to redesign the process to create standard and integrated processes. Action Research with a dual-cycle was the research paradigm. The Action component was to resolve the problem situation and the Research component was to acquire new knowledge. The researcher is not involved in the day-to-day running of the three subsidiary companies where the problem situation existed. The methodology used is the seven-stage Soft Systems Methodology. The research issues investigated are whether BPR can be used to resolve the problem situation, can a process-based organization be set-up with process owners and key performance indicators and whether dramatic improvements can be observed. The problem situation was expressed in As-Is context diagrams, activity-flow diagrams, organization charts, resulting in ""Rich Pictures"" drawing out the differences amongst the three subsidiary companies. Analysis of the As-Is data was carried out using the intervention analysis by means of the process-issues-classification method developed in this research as well as social and power analysis. Root definitions were developed for five macro processes. Conceptual To-Be' models were created for the business model, a process value chain, macro and micro processes, a process- based organization chart with process owners and key performance indicators. After the first cycle of Action Research, a strategic decision was taken to proceed along business specific units rather than group functions for order processing and credit management which were later merged. The To-Be models were compared to the As-Is models using the ordered questioning, general comparison and model outlay comparison methods. Outcome analysis is carried out where the important ideals are traced back through the analysis process to the point it is evaluable either quantitatively or qualitatively. Contribution to literature involved eight contributions from the BPR concept of standardization and integration, six in research methodology and three involving the BPR definition of dramatic improvements including the proposed guideline linking the level of process orientation in a company to the quantum change expected. This Action Research concludes that BPR can be used in the Malaysian context.